Neurological comorbidities and its association with gait speed in older adults of the Naval Medical Center Cirujano Mayor Santiago Távara 2010-2015. - Calderón-Campos, Karla M. (2019)
Objective: To determine the association between presence of neurological comorbidities and walking speed in older adults attended at the Naval Medical Center Cirujano Mayor Santiago Távara 2010-2015. Methods: Observational retrospective study through secondary analysis of a database of 1785 older adults. To determine the relationship between variables, the Chi-square test with a level of significance of 5%, and the STATA v.14 program were used. Results: 18.7% of the probands had Parkinsons disease, 44.9% had mild cognitive impairment, and only 3.1% had cerebrovascular disorder. There were significant differences in walking speed with respect to advanced age and female sex (greater in 80 y.o. or older females). There was a significant relationship between mild cognitive impairment and cerebrovascular disorder with walking speed. The probability of a slow walking speed adjusted for Parkinsons disease diagnosis, age and sex for those with mild cognitive impairment was 2.13 (IC95% 1.72-2.63), and for those with cerebrovascular disease, 1.79 (IC95% 1.01-3.20). Conclusions: Slow walking was presented mainly in women over 80 years of age, and was significantly related to mild cognitive impairment and cerebrovascular disorder, but not to Parkinsons disease